2019
DOI: 10.18632/oncotarget.27303
|View full text |Cite|
|
Sign up to set email alerts
|

SNiPER: a novel hypermethylation biomarker panel for liquid biopsy based early breast cancer detection

Abstract: IntroductionMammography is the gold standard for early breast cancer detection, but shows important limitations. Blood-based approaches on basis of cell-free DNA (cfDNA) provide minimally invasive screening tools to characterize epigenetic alterations of tumor suppressor genes and could serve as a liquid biopsy, complementing mammography.MethodsPotential biomarkers were identified from The Cancer Genome Atlas (TCGA), using HumanMethylation450-BeadChip data. Promoter methylation status was evaluated quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…In mammals, SPAG6 is predominately expressed in the sperm, lungs, nervous system and inner ear, and is considered to be mainly involved in sperm maturation and nervous system development under normal physiological conditions (11,12). Accumulating evidence has demonstrated that aberrant SPAG6 expression in hematological malignancies, and ovarian, bladder, breast and lung cancer, may affect the occurrence and development of human cancer types by regulating the proliferation, apoptosis, invasion and metastasis of tumor cells (13)(14)(15)(16)(17)(18)(19)(20). In addition, SPAG6 has been reported to enhance the effect of apoptosis-inducing drugs and induce cell cycle arrest (21).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, SPAG6 is predominately expressed in the sperm, lungs, nervous system and inner ear, and is considered to be mainly involved in sperm maturation and nervous system development under normal physiological conditions (11,12). Accumulating evidence has demonstrated that aberrant SPAG6 expression in hematological malignancies, and ovarian, bladder, breast and lung cancer, may affect the occurrence and development of human cancer types by regulating the proliferation, apoptosis, invasion and metastasis of tumor cells (13)(14)(15)(16)(17)(18)(19)(20). In addition, SPAG6 has been reported to enhance the effect of apoptosis-inducing drugs and induce cell cycle arrest (21).…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent review based on 14 studies, cfDNA methylation analysis is highly promising for both early detection and disease relapse [29]. Methylation of SPAG6, NKX2-6, ITIH5, and PER1 genes was detected early in serum of breast cancer patients [30].…”
Section: Early Detectionmentioning
confidence: 99%
“…Cancer-associated changes in DNA methylation can be identified in blood, stool, urine or other biofluids [ 110 , 111 ]. As was demonstrated by an example of breast cancer, blood-based approaches associated with cell-free DNA are minimally invasive screening tools used to define epigenetic alterations of genes serving as liquid biopsy, complementing conventional detection tools such as mammography [ 112 ]. Moreover, the detection of DNA methylation in plasma or serum samples may help to understand tumor heterogeneity better than tissue biopsy [ 89 ].…”
Section: Blood Samples As Currently Most Frequently Used Liquid Bimentioning
confidence: 99%
“…Moreover, the detection of DNA methylation in plasma or serum samples may help to understand tumor heterogeneity better than tissue biopsy [ 89 ]. An evaluation of promoter methylation in a serum test, serum validation, and a plasma cohort revealed that the promising potential for early breast cancer detection could be attributed to the novel hypermethylation biomarker panel including SPAG6 , NKX2-6 , ITIH5, and PER1 [ 112 ]. Additionally, the assessment of the methylation level of selected genes in circulating cell-free DNA in plasma samples may be considered an effective procedure for the subtyping of lung cancer in addition to standard diagnostic procedures [ 89 ].…”
Section: Blood Samples As Currently Most Frequently Used Liquid Bimentioning
confidence: 99%
See 1 more Smart Citation